Is patient empowerment the key to promote adherence? A systematic review of the relationship between self-efficacy, health locus of control and medication adherence. - Lilla Náfrádi; Kent Nakamoto; Peter J Schulz (PLoS ONE)
Background Current health policies emphasize the need for an equitable doctor-patient relationship, and this requires a certain level of patient empowerment. However, a systematic review of the empirical evidence on how empowerment affects medication adherence-the extent to which patients follow the physician's prescription of medication intake-is still missing. The goal of this systematic review is to sum up current state-of-the-art knowledge concerning the relationship between patient empowerment and medication adherence across medical conditions. As our conceptualization defines health locus of control and self-efficacy as being crucial components of empowerment, we explored the relationship between these two constructs and medication adherence. Methods Relevant studies were retrieved through a comprehensive search of Medline and PsychINFO databases (1967 to 2017). In total, 4903 publications were identified. After applying inclusion and exclusion criteria and quality assessment, 154 articles were deemed relevant. Peer-reviewed articles, written in English, addressing the relationship between empowerment (predictor) and medication adherence (outcome) were included. Findings High levels of self-efficacy and Internal Health Locus of Control are consistently found to promote medication adherence. External control dimensions were found to have mainly negative (Chance and God attributed control beliefs) or ambiguous (Powerful others attributed control beliefs) links to adherence, except for Doctor Health Locus of Control which had a positive association with medication adherence. To fully capture how health locus of control dimensions influence medication adherence, the interaction between the sub-dimensions and the attitudinal symmetry between the doctor and patient, regarding the patient's control over the disease management, can provide promising new alternatives. Discussion The beneficial effect of patients' high internal and concurrent physician-attributed control beliefs suggests that a so-called "joint empowerment" approach can be suitable in order to foster medication adherence, enabling us to address the question of control as a versatile component in the doctor-patient relationship.